Knowledge and Attitudes for the Management of Behavioral Variant of Frontotemporal Dementia - Castro-Suarez, Sheila; Guevara-Silva, Erik; Caparó-Zamalloa, César; Osorio-Marcatinco, Victor; Meza-Vega, Maria; Miller, Bruce; Cornejo-Olivas, Mario (Frontiers in Neurology, 2022)
Background: The diagnosis of the behavioral variant of frontotemporal dementia (bvFTD) can be especially challenging and is relatively underdiagnosed. There is scarce information on training and attitudes from care providers facing bvFTD in settings with limited resources. We aim to describe clinical knowledge and attitudes facing bvFTD from neurologists, psychiatrists, and residents in Peru. Methods: Potential participants received invitations by email to complete an online questionnaire. In addition, we reviewed 21 curricula from undergraduate medical schools’ programs offered by the main schools of medicine in Peru during 2020 and 2021. Results: A total of 145 participants completed the survey. The responders were neurologists (51%), psychiatrists (25%), and residents in neurology or psychiatry (24%). Only 26% of the respondents acknowledged receiving at least one class on bvFTD in undergraduate medical training, but 66.6% received at least some training during postgraduate study. Participants identified isolated supportive symptoms for bvFTD; however, only 25% identified the possible criteria and 18% the probable bvFTD criteria. They identified MoCA in 44% and Frontal Assessment Battery (39%) as the most frequently used screening test to assess bvFTD patients. Memantine and Acetylcholinesterase inhibitors were incorrectly indicated by 40.8% of participants. 76% of participants indicated that they did not provide education and support to the caregiver. The dementia topic was available on 95.2%, but FTD in only 19%. Conclusion: Neuropsychiatry medical specialists in Peru receive limited training in FTD. Their clinical attitudes for treating bvFTD require appropriate training focused on diagnostic criteria, assessment tools, and pharmacological and non-pharmacological management.